Lectotypification of Albizia thompsonii (Leguminosae: Mimosoideae) - Tiwari, Arjun Prasad (Phytotaxa, 2016)
The name Albizia thompsonii (Leguminosae: Mimosoideae) is herewith typified with a specimen at K, and this selection constitutes the second-step of the lectotypification. A photograph of the selected lectotype is provided.